Evaluasi uji saring hepatitis B reaktif pada darah donor tahun 2019 di UTD PMI kota Malang - Pri Irani, Dahlia Ayu; Rohman, Hendra; Rahmatullah, Widia (MEDIA ILMU KESEHATAN, 2021)
Background: Screening tests for infectious infections through blood transfusion (IMLTD) are one of the blood safeguards carried out at the Blood Transfusion Unit. Hepatitis B is one of the infectious diseases that must be examined. Objective: It aims to evaluate IMLTD, identify the types of donors that show reactive hepatitis B based on new donors and routine donors, identify causes based on input, process, output whether true or false reactive, and counseling reactive donors. Methods: Descriptive research with a quantitative approach. Population is 49,379 donors in 2019 (0.0052%), sample is 256 donors. Primary and secondary data were taken at UTD PMI Malang City then a questionnaire was made and an evaluation was carried out. Results: Evaluation of reactive hepatitis B screening tests based on the evaluation of the number of blood donors with reactive hepatitis B obtained the types of donors, namely new donors (55%) and routine donors (44%). Evaluation based on input and output obtained donor blood samples according to the required criteria (100%). Evaluation process for officers, methods, reagents, and room conditions with good results (100%), while the suitability of the tools (97.23%). Hepatitis B reactive donors who did counseling (17.2%). Conclusion: UTD PMI Malang City which has been certified CPOB BPOM RI can maintain the quality and consistency of the quality of blood services, especially in the hepatitis B reactive donor counseling service. Evaluation results of hepatitis B filter test are true reactive and consistency is needed in maintaining quality policy is needed for donor counseling.